Asymmetric Mobility and Emigration of Highly Skilled Workers in Europe: The Portuguese case - Gomes, Rui Machado (2018)
Emigration is a chronic structural process of the Portuguese society. The discussion and key arguments raised in this chapter are mainly focused on data from a research project on Portuguese skilled emigration. Based on the outcomes of the BRADRAMO2 on-line survey to 1011 highly skilled emigrants it can be suggested that recent phenomena in general, and the crisis that began around 2008 in particular, profoundly transformed the patterns of Portuguese emigration. Nowadays, the country faces a brain drain dynamic that is dramatically altering the profles of national emigrants, emigration destinations, self-identity, and the strategies of those who leave the country. Academic mobility, mainly that promoted by the European Union (through grants from the Erasmus Program), created and fostered mobility ﬂows that reinforced a latent mobility phenomenon. Once engaged in academic mobility programs, Portuguese higher education students tend to stay in the country of destination or, upon returning temporarily to Portugal, to evince a very strong predisposition to move to a country of the European Union. The profle of Portuguese high-skilled emigrants reveals a trend towards a permanent and a long-term (as opposed to a temporary or transitory) mobility, an insertion in the primary segment of the labor market of the destination countries, a predominance of professionals connected to the academic/scientifc system and to professions requiring high skills, and a latent mobility (afer a period of study in the country of destination) rather than direct mobility ﬂows (afer having entered in the employment system of the sending country).